Friday

April 18, 2014

April 18, 2014

Posted by **Shawn** on Friday, November 28, 2008 at 2:48am.

- Algebra help -
**drwls**, Friday, November 28, 2008 at 9:50amFor f(of)g(x), take (2x+3) - (2x+3)^2

(insert g(x) where the "x" is in f(x) )

For g(of)f(x), take 2[x-x^2] +3

**Related Questions**

Algebra 2 - If f(x) = x-3 g(x) = 2x+5 find fog and gof

Algebra - If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (...

Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3. Okay so I ...

college algebra - 1. answer the following for the given quadratic function f(x)=...

Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...

Calculus - Hi there, I need help with composition of functions. I need to find ...

math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5

Math - Find (fog)(2) f(x)=Squareroot 4-x; g(x)=1-3x^2 Find (gof)(-2) for the ...

math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5

Math - Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show ...